KAJIAN KETERSAMBUNGAN SANAD (ITTIŞĀL AL-SANAD) - Muhammad Anshori (Jurnal Living Hadis, 2016)
The study of sanad’s quality was so broad then implies to the existence of ittiṣāl and inqiṭā’ al-sanad. The muttaṣi al-sanad hadith might be claimed a probable ṣahih when it is examined with al-jarḥ wa al-ta’dīl. In line to that, the muttaṣi al-sanad might be also questioned about the linked riwayat to Nabi (marfū’), as there were also some hadith which linked the sanad to sahabat (mauqūf) or tabi’in (maqṭū’). And so does to the term fake hadith within ilmu al-Muṣṭalaḥ al-Ḥadīṡ which is called mauḍū’. This paper then starts to problematize why it is so important to study the level of fake hadith while at the same time a counter statement says that it came from a concept brought by former ulama and agreed by most today’s ulama. In another part, this paper argues that the term ittiṣāl al-sanad may be applied or contextualized in daily life, specifically within educational concern as long as academia within this study elaborate a broader scope, such as both matan and sanad field of study.